2018
DOI: 10.1002/jbm.a.36325
|View full text |Cite
|
Sign up to set email alerts
|

Genipin‐cross‐linked type II collagen scaffold promotes the differentiation of adipose‐derived stem cells into nucleus pulposus‐like cells

Abstract: Adipose-derived stem cells (ADSCs)-based tissue engineering was a promising method to treat intervertebral disc degeneration. Type II collagen is a native component in the nucleus pulposus (NP), and has the ability to promote ADSCs to differentiate into NP-like cells. In this article, we aimed to establish a genipin-cross-linked three-dimensional (3D) type II collagen scaffold, and determine the biological effects of the scaffold on ADSCs differentiating into a NP-like phenotype. Different concentrations of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 46 publications
0
33
0
1
Order By: Relevance
“…Similarly, Shh protein expression level has also been shown an increase when crosslinked scaffolds promoted ADSC proliferation and differentiation into NP-like cells, indicating that the activation of the Shh signaling pathway might play a regulatory role in directional differentiation (Zhou et al, 2018b). In addition, NP-like cell differentiation induced by Collagen type II is related to FoxA2 overexpression and can be rescued by a Shh signaling pathway inhibitor (Zhou et al, 2018a).…”
Section: Signaling Pathways Involved In Biomaterial-induced Ivd-like mentioning
confidence: 97%
See 2 more Smart Citations
“…Similarly, Shh protein expression level has also been shown an increase when crosslinked scaffolds promoted ADSC proliferation and differentiation into NP-like cells, indicating that the activation of the Shh signaling pathway might play a regulatory role in directional differentiation (Zhou et al, 2018b). In addition, NP-like cell differentiation induced by Collagen type II is related to FoxA2 overexpression and can be rescued by a Shh signaling pathway inhibitor (Zhou et al, 2018a).…”
Section: Signaling Pathways Involved In Biomaterial-induced Ivd-like mentioning
confidence: 97%
“…Thus, to mimic the natural structure of IVD tissues, collagen I/II are widely used materials for IVD regeneration. However, biomaterials consisting of collagen alone are less efficient in promoting stem cell differentiation toward IVD cells, and supplementation with crosslinking agents of appropriate concentration is more likely to increase adipose-derived stem cells (ADSCs) gene and protein expression of Collagen type II, Sox-9 and aggrecan, suggesting a NP-like phenotype (Zhou et al, 2018b). Gelatine, which is a denatured form of collagen, has been used for NP-like differentiation of ADSCs and IVD repair.…”
Section: Natural Biomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases, gelatin and collagen were used as an additional composite with other materials to improve biomechanical and metabolic properties [85,86,87]. Human AF cells have good adhesion and increased anabolic activity in fibronectin, collagen, and gelatin substrate.…”
Section: Treatment For Degenerative Ivdmentioning
confidence: 99%
“…This evidence indicates that FoxA2 is important in generating NP cells. We have demonstrated that type II collagen increases the expression of FoxA2 in ADSCs during NP-like differentiation (22). An investigation of the function of FoxA2 and the relationship between FoxA2 and Shh signaling is needed to clarify the mechanism of type II collagen-induced NP-like differentiation of ADSCs.…”
mentioning
confidence: 95%